CRISPR/cas Loci of Type II Propionibacterium acnes Confer Immunity against Acquisition of Mobile Elements Present in Type I P. acnes - Brüggemann, Holger (Public Library of Science, 2012)

(untitled)
Propionibacterium acnes is a skin commensal that occasionally acts as an opportunistic pathogen. The population structure of this species shows three main lineages (I–III). While type I strains are mainly associated with sebaceous follicles of human skin and inflammatory acne, types II and III strains are more often associated with deep tissue infections. We investigated the occurrence and distribution of the clustered regularly interspaced short palindromic repeats (CRISPR) in P. acnes, assessed their immunological memory, and addressed the question if such a system could account for type-specific properties of the species. A collection of 108 clinical isolates covering all known phylotypes of P. acnes was screened for the existence of CRISPR/cas loci. We found that CRISPR loci are restricted to type II P. acnes strains. Sequence analyses of the CRISPR spacers revealed that the system confers immunity to P. acnes-specific phages and to two mobile genetic elements. These elements are found almost exclusively in type I P. acnes strains. Genome sequencing of a type I P. acnes isolate revealed that one element, 54 kb in size, encodes a putative secretion/tight adherence (TAD) system. Thus, CRISPR/cas loci in P. acnes recorded the exposure of type II strains to mobile genetic elements of type I strains. The CRISPR/cas locus is deleted in type I strains, which conceivably accounts for their ability to horizontally acquire fitness or virulence traits and might indicate that type I strains constitute a younger subpopulation of P. acnes.